Present-Day Lake Level Variation from Envisat Altimetry over the Northeastern Qinghai-Tibetan Plateau: Links with Precipitation and Temperature - Lee, Hyongki; Shum, C. K.; Tseng, Kuo-Hsin; Guo, Jun-Yi; Kuo, Chung-Yen (Chinese Geoscience Union, 2011)
Lakes in permafrost regions are highly sensitive to changes in air temperature, snowmelt, and soil frost. In particular, the Qinghai-Tibetan Plateau (QTP) is one of the most sensitive regions in the world influenced by global climate change. In this study, we use retracked Enivsat radar altimeter measurements to generate water level change time series over Lake Qinghai and Lake Ngoring in the northeastern QTP and examine their relationships with precipitation and temperature changes. The response of water levels in Lake Qinghai and Lake Ngoring is positive with regards to precipitation amount. There is a negative relationship between water level and temperature change. These findings further the idea that the arid and high-elevation lakes in the northeastern QTP are highly sensitive to climate variations. Water level increases in Lake Qinghai in winter may indicate inputs of subsurface water associated with freeze-thaw cycles in the seasonally frozen ground and the active layer.